Impact of tax progressivity on regional income inequalities: a comparative analysis between Brazil and Germany - RAIHAN MIAN; SWARNA BINTAY KADIR; DIEGO SANCHES CORRÊA (Brazilian Journal of Political Economy)
ABSTRACT The progressivity of a country’s tax system can be crucial for reducing income and regional inequalities. Focusing on the cases of Germany and Brazil, in this article we analyze the tax system progressivity through an original indicator based on the Personal Income Tax (PIT) and the Value Added Tax (VAT) to determine its association with income and regional inequalities at the national and sub-national levels. We show that a progressive tax system reduces income and regional inequalities.